2016
DOI: 10.1080/00224545.2015.1135865
|View full text |Cite
|
Sign up to set email alerts
|

When less equal is less human: Intragroup (dis)respect and the experience of being human

Abstract: Past research has demonstrated that equality-based respect is an important antecedent of positive social interaction and group-serving behavior. In the present research we tested whether intragroup equality-based respect affects perceptions of being treated as a human as well as self-dehumanization. In Experiment 1, we found that high respect received from fellow work group members heightens group members' sense of being treated as a human being, while low respect diminishes it. In Experiment 2, we secured evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
1
24
0
3
Order By: Relevance
“…In our view, equality‐based respect represents a promising bottom‐up way in order to arrive at a global identity that people actually feel because it results from their personal experience of being an equal actor (see also Batalha & Reynolds, , p. 754). This type of respect with its focus on equal basic rights enables personal autonomy as self‐determination (Renger et al, ) and is thus compatible with interpersonal differences and diversity—a prerequisite for an authentic global identity (see also Rosenmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our view, equality‐based respect represents a promising bottom‐up way in order to arrive at a global identity that people actually feel because it results from their personal experience of being an equal actor (see also Batalha & Reynolds, , p. 754). This type of respect with its focus on equal basic rights enables personal autonomy as self‐determination (Renger et al, ) and is thus compatible with interpersonal differences and diversity—a prerequisite for an authentic global identity (see also Rosenmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Three items were used from Renger et al (): “Other people behave towards me in a very caring manner”; “Other persons show unconditional affection towards me”; and “Other persons always satisfy my emotional needs” (α = .81).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first evidence pointing to this internalization process was demonstrated by research associating equality‐based respect with self‐humanization processes (Renger, Mommert, Renger & Simon, ), perceptions of personal autonomy (Renger et al, ), and self‐determination (Decker & Van Quaquebeke, ). Research has demonstrated that equality‐based respect can come from different sources including ingroups (Renger & Simon, ), outgroups (Simon, Mommert, & Renger, ), or more generally from individuals relevant in one’s life (Renger & Reese, ).…”
Section: Antecedents Of Self‐respectmentioning
confidence: 99%